Pembinaan dan Sertifikasi Pertanian Organik (Komoditi Padi) di Kabupaten Semarang - Supriyadi Supriyadi; Sumani Sumani; Joko Winarno; Sri Hartati; Jauhari Syamsiah (Jurnal Sinergitas PKM & CSR, 2016)
AbstractBackground, excessive exploitation of paddy land in the long term without the addition of organic matter have resulted in soil become damaged. To meet the needs of food (rice) healthy and improve the functioning of the land, then there is no best alternative except development of organic farming systems. To be able to implement a system of organic farming, it is necessary to institute internal quality assurance. Internal Control System for the establishment of needed care and support of various Stakeholders, Universities and the Institute for Certification of organic products. To realize the organic product certification program, so it will need the presence of the CSR programs of various Stakeholders and Businesses. The purpose, carry out assistance to Farmers and Farmers Group in the establishment of the ICS and the acquisition of organic certification. The method, is Focus Group Discussion which emphasizes dialogue interpersosnal and mentoring. Results, an increasing number of farmers' groups who implement the organic certification of 4 (four) farmer groups (40,59Ha) to 10 farmer groups (132,241Ha). In conclusion, most members of the Farmers Group Al-Barokah have felt: (a) the benefit of the treatment of organic in terms of soil quality and the products of organic rice and its by-products, (b) an increase in value-added organic products and farmers' income, (c) the importance of maintaining paddy according to its function, (d) have become independent farmers in organic rice cultivation.Keywords:  Organic farming systems, Organic certification, Interpersonal dialogue, Corporation Social Responsibility (CSR)AbstrakLatar belakang, eksploitasi tanah sawah yang berlebihan dalam jangka waktu lama tanpa penambahan bahan organik telah mengakibatkan tanah menjadi rusak. Untuk mencukupi kebutuhan pangan (padi) yang sehat dan meningkatkan fungsi tanah, maka tidak ada alternatif terbaik kecuali pengembangan sistem pertanian organik.  Untuk dapat melaksanakan sistem pertanian organik, maka diperlukan lembaga penjaminan mutu internal. Untuk pembentukan Internal Control Sistem diperlukan adanya kepedulian dan dukungan dari berbagai pemangku kebijakan, Perguruan Tinggi dan Lembaga Sertifikasi produk organik. Untuk mewujudkan program sertifikasi produk organik, maka sangat diperlukan keberadaan program CSR dari berbagai pemangku kepentingan dan pelaku bisnis. Tujuan, melaksanakan pendampingan terhadap Kelompok Tani dan Gabungan Kelompok Tani dalam pembentukan ICS dan perolehan sertifikasi organik. Metode, FGD yang mengedepankan dialog interpersosnal, pendampingan. Hasil, terjadi peningkatan jumlah kelompok tani yang melaksanakan sertifikasi organik dari 4 (empat) kelompok tani (luas 40,59Ha) menjadi 10 kelompok tani  (132,241Ha). Simpulan, sebagian besar anggota Gabungan Kelompok Tani Al-Barokah telah merasakan: (a) manfaatan perlakuan organik dari segi kualitas tanah dan produk padi organik serta produk sampingannya, (b) adanya peningkatan nilai tambah produk organik dan pendapatan petani, (c) pentingnya mempertahankan sawah sesuai fungsinya, (d) telah menjadi petani yang merdeka dalam budidaya padi organik.Kata kunci:  Sistem pertanian organik,  Sertifikasi organik, Dialog interpersonal, Corporation Social Responsibility (CSR)